2020
DOI: 10.1177/1756284820910659
|View full text |Cite
|
Sign up to set email alerts
|

Automated endoscopic detection and classification of colorectal polyps using convolutional neural networks

Abstract: Background: Recently the American Society for Gastrointestinal Endoscopy addressed the ‘resect and discard’ strategy, determining that accurate in vivo differentiation of colorectal polyps (CP) is necessary. Previous studies have suggested a promising application of artificial intelligence (AI), using deep learning in object recognition. Therefore, we aimed to construct an AI system that can accurately detect and classify CP using stored still images during colonoscopy. Methods: We used a deep convolutional ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 37 publications
1
63
0
3
Order By: Relevance
“…All 4245 studies were screened and 106 full-length articles and/or abstracts were assessed. Nineteen studies 2 5 6 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 reported on the detection and/ or classification of gastrointestinal neoplastic lesions by CNN. Among the 19 studies, five 6 12 15 17 26 reported on efficacy of CNN in diagnosing esophageal neoplasia, eight 5 14 16 18 19 22 23 25 reported on use of CNN in neoplasia of the stomach and six 2 11 13 20 21 24 evaluated use of CNN in diagnosing colorectal neoplasia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 4245 studies were screened and 106 full-length articles and/or abstracts were assessed. Nineteen studies 2 5 6 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 reported on the detection and/ or classification of gastrointestinal neoplastic lesions by CNN. Among the 19 studies, five 6 12 15 17 26 reported on efficacy of CNN in diagnosing esophageal neoplasia, eight 5 14 16 18 19 22 23 25 reported on use of CNN in neoplasia of the stomach and six 2 11 13 20 21 24 evaluated use of CNN in diagnosing colorectal neoplasia.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies 2 5 6 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 reported on the detection and/ or classification of gastrointestinal neoplastic lesions by CNN. Among the 19 studies, five 6 12 15 17 26 reported on efficacy of CNN in diagnosing esophageal neoplasia, eight 5 14 16 18 19 22 23 25 reported on use of CNN in neoplasia of the stomach and six 2 11 13 20 21 24 evaluated use of CNN in diagnosing colorectal neoplasia. Seven studies 5 11 12 14 19 20 25 used standard WLE, eight used NBI (magnifying and/ or non-magnifying) 2 6 13 15 18 22 23 26 and four 16 17 21 24 used a combination of standard WLE and/or NBI and/or chromo-endoscopy images ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ], and Ozawa et al . [ 18 ] have the data of diminutive CPs. We thought it was not appropriate to add theme to the general analysis for the potential risk of duplication of data.…”
Section: Methodsmentioning
confidence: 99%
“…A Japanese study group has proposed simultaneous polyp detection and characterization by using the technologies they have developed: (i) an algorithm based on a deep‐learning algorithm for detecting polyps in white‐light images; and (ii) another algorithm that predicts a polyp's pathology and was designed for endocytoscopic images obtained by taking a photograph with the tip of the endoscope in contact with the polyp 61 . Ozawa et al 62 . reported similar systems using a Single Shot MultiBox Detector that can detect and characterize a target object simultaneously (Fig.…”
Section: Simultaneous Usage Of Cade and Cadxmentioning
confidence: 99%